Diversified human resource allocation significantly enhances plant community species diversity and ecosystem stability (Bangladesh Journal of Botany, 2026)
The purpose of this study was to investigate how the diversified allocation of human resources under the catalyst of green human resource management (GHRM) system, affects the strategy selection of ecological management teams and ultimately shapes the ecological indicators of plant communities. In view of the scarcity of long-period empirical data, this study constructed a simulation experimental framework covering 1000 samples of ecological restoration projects, and used partial least squares structural equation modeling (PLS-SEM) to conduct full path analysis. The results showed that gender and cultural tolerance significantly enhanced the post-disaster resilience and long-term stability of ecosystems. Further, break through the traditional myth of "building the nest and guiding the bird", quantify the decisive power of human management driving effects on the reshaping of nature, and provide a new guide based on human capital optimization for global biodiversity conservation and corporate environmental, social and governance (ESG) strategies.Bangladesh J. Bot. 55(2): 279-286, 2026 (June)